Intestinal Microorganisms of Termites and Other Invertebrates - König, Helmut; Varma, Ajit (Soil Biology, 2006)
Soil microorganisms play a major role in the degradation and recycling of organic material. Microbes are involved in the food web and strongly contribute to soil fertility. In the past, attention was mainly directed towards free-living or particle-bound microorganisms, while the role of intestinal microbes of soil animals has been neglected. For the first time, "Intestinal Microorganisms of Termites and Other Invertebrates" focuses on the microbes in gut systems of soil animals. It starts with a profound overview of the biology of soil invertebrates. A major part deals with the gut microbiota of termites, the best investigated gut system of invertebrates. Termites are important soil processors in tropical and subtropical regions. Insight is given into the intestinal microbiota of further relevant primary litter decomposers, such as earthworms, springtails, millipeds, and woodlice. Novel techniques for studying intestinal microbes complete the volume.